2021
DOI: 10.1039/d0dt03856c
|View full text |Cite
|
Sign up to set email alerts
|

Testing the reversible insertion of magnesium in a cation-deficient manganese oxy-spinel through a concentration cell

Abstract: A new electrochemical procedure to explore the intercalation of magnesium using a concentration cell with two cubic spinels Mg1−xMn2O4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Recent studies found a phase intermediate between MgMn 2 O 4 and λ‐MnO 2 , [7f] although it could be affected by kinetics effects. We found that for partially demagnesiated Mg x Mn 2 O 4 , the Mn‐vacancies can decrease the cell polarization [7g] . Other authors studied the relevant role of water content in the electrochemistry of MgMn 2 O 4 [11] …”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…Recent studies found a phase intermediate between MgMn 2 O 4 and λ‐MnO 2 , [7f] although it could be affected by kinetics effects. We found that for partially demagnesiated Mg x Mn 2 O 4 , the Mn‐vacancies can decrease the cell polarization [7g] . Other authors studied the relevant role of water content in the electrochemistry of MgMn 2 O 4 [11] …”
Section: Introductionmentioning
confidence: 62%
“…The partial demagnesiation of MgMn 2‐y Fe y O 4 nanoparticles was performed by using acid‐treatment [6a,7g,14] . The raw sample was added to a solution of nitric acid at pH=2 with continue stirring for two hours.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations